The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/1099-0739(200010)14:10<644::aid-aoc53>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Bis(diphenylphosphino)-ferrocene or -dicarba-closo-dodecaborane as ligands in gold and silver chemistry

Abstract: The synthesis and properties of gold and silver complexes with bis(diphenylphosphino)-ferrocene or -dicarba-closo-dodecaborane, and other related derivatives, such as the corresponding partially degraded nido-carborane or bis{di-phenylthio(or seleno)phosphoryl}ferrocene, as ligands are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Gold and silver chemistry with (PPh 2 ) 2 C 2 B 10 H 10 (dppcc) has been reviewed [8]. From the reaction of [Au(tht) 2 ]ClO 4 (tht = tetrahydrothiophene) or AgClO 4 with dppcc complexes [Au(tht)(dppcc)]ClO 4 or [Ag(OClO 3 )(dppcc)] are obtained.…”
Section: Complexes With Phosphine Ligandsmentioning
confidence: 99%
“…Gold and silver chemistry with (PPh 2 ) 2 C 2 B 10 H 10 (dppcc) has been reviewed [8]. From the reaction of [Au(tht) 2 ]ClO 4 (tht = tetrahydrothiophene) or AgClO 4 with dppcc complexes [Au(tht)(dppcc)]ClO 4 or [Ag(OClO 3 )(dppcc)] are obtained.…”
Section: Complexes With Phosphine Ligandsmentioning
confidence: 99%
“…[1] It could be the main reason for the less explored chemistry of acyl phosphines when compared with that of other tertiary phosphine ligands. [2][3][4][5][6][7][8][9] Nevertheless, they are recently used as phosphine sources in catalytic C-P bond forming reactions. [10][11][12][13][14] It is observed that the P-C(O) bond lengths in acyl phosphines and di (acyl) phosphines are slightly longer than those of P-C (sp 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4 The dppf is a biphosphine ligand and can adopts numerous coordination modes in complexes of a range of transition metals. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These dppf complexes have been utilized in several area such as catalysis, materials science, electrochemistry, and biology. 1,2,7,9,10,[19][20][21] On the other hand, the chemistry of cyclometalated complexes is of great interest because of their use in a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%